Жарким летом: Рассказы / Ф. А. Абрамов - Абрамов Федор Александрович (Сов. писатель, 1984)
Экземпляры: ФО-1 (20160425) / Инвентарный номер: 8125 / Сис.шифр: Р2 / Авт.знак: А16 / ГРНТИ: 17.82 / ББК: Р2